Geospatial analysis of water uses and potential conflicts in the microregion of Ceres, Goiás, Brazil - Barreto, Cristiane Gomes; Rodrigues, Renato Arthur Franco; Drummond, José Augusto Leitão (Sustainability in Debate, 2019)
Conflicts related to water have been expanding around the world, especially in areas which experience rapid changes in land use and occupation. The Ceres microregion (Goiás) has passed by an accelerated process of sugar cane agroindustrialization in recent years and water scarcity problems has been percieved. This work contributes to understand potential environmental conflicts related to water resources in Ceres microregion by the evaluation of the ways, intensity and spatial distribution of water consumption in differents basins of the microregion. It was analyzed secondary data from water demands, sugar and alcohol production, irrigation and others from geostatistic tools. The results suggest that sugar cane crops have a strong impact over water consumption, although this activity is not related to the water deficit in most of the basins, what suggests it is not responsible for situations of water scarcity or conflicts associated to shortages.